Gasdermin D inhibition prevents multiple organ dysfunction during sepsis by blocking NET formation - Silva, Camila Meirelles S.; Wanderley, Carlos Wagner S.; Veras, Flavio P.; Sonego, Fabiane; Nascimento, Daniele C.; Gonçalves, Augusto V.; Martins, Timna V.; Cólon, David F.; Borges, Vanessa F.; Brauer, Verônica S.; Damasceno, Luis Eduardo A.; Silva, Katiussia P. [UNESP]; et al. (American Society of Hematology, 2021)
Multiple organ dysfunction is the most severe outcome of sepsis progression and is highly correlated with a worse prognosis. Excessive neutrophil extracellular traps (NETs) are critical players in the development of organ failure during sepsis. Therefore, interventions targeting NET release would likely effectively prevent NET-based organ injury associated with this disease. Herein, we demonstrate that the pore-forming protein gasdermin D (GSDMD) is active in neutrophils from septic humans and mice and plays a crucial role in NET release. Inhibition of GSDMD with disulfiram or genic deletion abrogated NET formation, reducing multiple organ dysfunction and sepsis lethality. Mechanistically, we demonstrate that during sepsis, activation of the caspase-11/GSDMD pathway controls NET release by neutrophils during sepsis. In summary, our findings uncover a novel therapeutic use for disulfiram and suggest that GSDMD is a therapeutic target to improve sepsis treatment.